2019
DOI: 10.1088/1742-6596/1242/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate treatment of coir fiber on wettability and shear strength of coir fiber-epoxy composite

Abstract: This research presented the influence of treated coir fiber with sodium bicarbonate on wettability and interfacial shear strength (IFSS) of coir fiber-epoxy composite. Coir fibers were immersed in the solution of sodium bicarbonate with three different densities (8wt%, 10wt%, and 12wt %) for 24 hours and 120 hours. Epoxy resin was utilized as a matrix of composite. Wettability and IFSS of coir fiber-matrix adhesion were evaluated. Fiber wettability to the matrix was performed by measuring the droplet contact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sair et al [ 28 ] confirmed that the chemical alteration of hemp fiber with alkali and silane coupling agent improved the hemp fiber's thermal conductivity and also improved the composites' tensile strength and young's modulus. Bakri et al [ 29 ] investigated the effect of NaHCO 3 treatment of coir fiber on the wettability and interfacial shear strength of coir fiber reinforced epoxy composites. They discovered that the NaHCO 3 treatment of the coir fiber has effectively improved the wettability between the fiber and the matrix and also enhanced the interfacial shear strength of the treated coir/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…Sair et al [ 28 ] confirmed that the chemical alteration of hemp fiber with alkali and silane coupling agent improved the hemp fiber's thermal conductivity and also improved the composites' tensile strength and young's modulus. Bakri et al [ 29 ] investigated the effect of NaHCO 3 treatment of coir fiber on the wettability and interfacial shear strength of coir fiber reinforced epoxy composites. They discovered that the NaHCO 3 treatment of the coir fiber has effectively improved the wettability between the fiber and the matrix and also enhanced the interfacial shear strength of the treated coir/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…The surface treatment of oil palm mesocarp fiber was conducted to improve the binding of fiber and matrix. 12 wt% NaHCO3 solution was used to immersion of fiber during 120 hours at room temperature [7,8]. Fiber then was cleaned after immersion and dried during 24 hours in room temperature.…”
Section: Surface Treatment Of Fibersmentioning
confidence: 99%
“…They found the phosphate salt treatment was most effective in improving the thermal stability of jute fibre polymer composite. Bakri et al [17] examined the wettability and interfacial shear strength of coir fibre-reinforced epoxy composites after treating the coir fibre with NaHCO 3 . They observed that treating the coir fibre with NaHCO 3 increased the interfacial shear strength of the treated coir/epoxy composites while also improving the wettability between the fibre and the matrix.…”
Section: Introductionmentioning
confidence: 99%